III Zjazd Komisji Historii Starożytnej Polskiego Towarzystwa Historycznego (KHS PTH) z Ogólnopolską Konferencją Naukową „Przestrzenie antyku” (Białystok, 17-19.09.2025) - Kochanek, Piotr (Vox Patrum, 2025)
Report from the 3rd Congress of the Commission on Ancient History of the Polish Historical Society with the National Scientific Conference „Spaces of Antiquity” that took place in Białystok, Poland on 17-19.09.2025.